2019
DOI: 10.1108/ijwhm-07-2018-0089
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the injured worker’s experience and relationship with the workplace return to work coordinator in NSW, Australia

Abstract: Purpose The purpose of this paper is to provide insight into the injured worker’s perspective of experiences with their workplace return to work coordinator (RTWC), and explore some of the barriers they encountered in the return to work process. Design/methodology/approach Semi-structured interviews were conducted with ten injured workers from New South Wales, Australia. The thematic analysis of transcripts was completed. Findings The findings provide an insight into the experiences of injured workers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Regarding the empirical findings, Pransky et al [ 11 ], in line with our findings, reported professional credibility and administrational skills as important, and being knowledgeable about legal aspects as well as medical conditions have been reported as important by Shaw et al [ 9 ]. Bohatko-Naismith et al [ 13 , 17 ] found, similar to our findings, that good communication skills and empathy were important characteristics/traits to have. Some of the highest ranked competencies from Pransky et al’s [ 11 ] study (e.g., being committed to the goal of an early RTW) were not mentioned by our participants, while some of their lowest ranked competencies (e.g., taking a client-centred approach and the ability to evaluate potential impacts of co-morbidity) were important findings in our study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding the empirical findings, Pransky et al [ 11 ], in line with our findings, reported professional credibility and administrational skills as important, and being knowledgeable about legal aspects as well as medical conditions have been reported as important by Shaw et al [ 9 ]. Bohatko-Naismith et al [ 13 , 17 ] found, similar to our findings, that good communication skills and empathy were important characteristics/traits to have. Some of the highest ranked competencies from Pransky et al’s [ 11 ] study (e.g., being committed to the goal of an early RTW) were not mentioned by our participants, while some of their lowest ranked competencies (e.g., taking a client-centred approach and the ability to evaluate potential impacts of co-morbidity) were important findings in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Our purpose was not to define the right professional competence, or the right competences for a RECO to have; instead, our focus was to explore the patient perspective on this. The findings add to previous literature, for example, [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] by pointing to six different themes of competence, including both general and specific qualities as well as more symbolic aspects of competence, such as how the RECO appeared or acted. The six themes found were: communicative and coordinating skills, engagement and advocacy skills, advisory and guidance skills, being empathic and therapeutic, being persistent and flexible, and being professional and trustworthy.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…With the advancement of knowledge in the field, researchers have begun to realise the benefits of DM practices (Reynolds et al, 2006;Gail Hepburn et al, 2010). These benefits include improved employee health and safety and improved employee morale (Harder and Scott, 2005;Carmichael et al, 2016;Bohatko-Naismith et al, 2019). Other incentives for DM include corporate cultural incentives (Geisen et al, 2008) and the ability to generate additional business opportunities and reduce DM costs (Amick et al, 2000;Ngai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%